Assessment of Accessible Toilets for Differently Abled People: A Case Study on Inclusivity and Compliance - , Aysha Be, Promilakrishna Chahal (Archives of Current Research International, 2025)
The current study was designed to investigate the infrastructure barrier in building’s toilets and develop potential solutions for making infrastructure accessible to all. People with disability are on the rise around the world, and they're linked to the many other health issues like mental illness, cardiovascular disease, respiratory sickness and injury, cancer. the accessibility of differently abled students as compared to without disabilities for overall participation and academic achievements in higher education in the state of Andhra Pradesh. It was found from the study that differently abled students take more time to meet the demands of their studies, often used computers and information technology and have less participation in social and extracurricular activities. The study was carried out in Chaudhary Charan Singh Haryana Agricultural University, to find out the accessibility as per differently abled people. Seven buildings (College of Community Science, College of Agriculture, College of Agricultural Engineering, College of Basic Sciences and Humanities, Nehru Library, I.G. Auditorium and Fletcher Bhawan) of CCSHAU, Hisar were taken as the locale of the research. From the findings, door width of toilet in COBS&H ( \(\bar{x}\) =70.7±1.2 cm), Nehru Library ( \(\bar{x}\) =76.2±1.2 cm), F.B ( \(\bar{x}\) =66.3±0.2 cm) and in I.G auditorium ( \(\bar{x}\) =63.2±1.3 cm) was found to be less than recommended dimensions (90-100 cm) whereas in rest of the buildings (COCS, COA, COAE) door width was apropriate and correlated with recommended dimensions. The feature of kick plate was not provided in any of the toilet door while colour of the toilet door in I.G. Auditorium was not found to contrast in colour with the wall. Special toilets for differently abled people were found to be in COCS, COA and COAE but it was lacking in the rest of the buildings so western toilets were studied during the research. Roughed ceramic tiles were used in the toilets, which prevents the floor from being slippery while guiding blocks and tilted mirrors were not found in any of the buildings, even though mirror height was significantly (‘t'=4.1) higher than the recommended dimensions (90 cm) in all of them. Further, the floor area within the toilet was measured and found that sufficient space was provided for easy manoeuvring in COCS, COA, and COAE, which was significantly correlated with the recommended dimensions. There was no emergency alarm in any of the buildings. At least one special toilet should be provided on the ground floor of each building with proper space for manoeuvring of wheelchair person.